Global Utilisation Rate: A Predisposing Factor to Pupils’ Academic Achievement in Lagos State Primary Schools, Nigeria - Onilude, Olusegun Adeniran; Akinyemi, Isiaka Adeniran; Gbenu, Jide Pius (Journal of Educational Sciences, 2025)
The goal of this study was to determine the global utilisation rate as a predictor of pupils’ academic achievement in Lagos State's public primary schools. The study used a descriptive research approach, with 100 primary schools serving as the sample and 1020 public primary schools as the population. Sixty primary schools from the urban centre and 40 from the rural centre were chosen using a stratified sample technique. Since the data obtained already existed in the schools, Record Observations Formats were utilised to gather data. Inferential statistics were used to assess the null hypotheses. Some of the results indicated that there was a positive and non-significant relationship between global utilisation rate and pupils’ academic achievement in Lagos State; and no significant difference in class size, global utilisation rate, or pupils’ academic achievement in public primary schools in Lagos State. According to the study's findings, pupils’ academic achievement in public primary schools in Lagos State, Nigeria, is not significantly influenced by the global utilisation rate, which includes both time and space utilisation rates. Additionally, the survey found no difference in class size, global utilisation rate, or pupils’ academic achievement across public primary schools in rural and urban areas. Therefore, the study advised that policymakers like SUBEB and UBEC enforce and guarantee the application of the policies developed in relation to a particular number of pupils in the classrooms and the necessary classroom dimensions in elementary schools.